Unsavory truth : how food companies skew the science of what we eat - Nestle, Marion (Basic Books, 2018)
"Is chocolate heart-healthy? Does yogurt prevent type 2 diabetes? Do pomegranates help cheat death? News accounts bombard us with such amazing claims, report them as science, and influence what we eat. Yet, as Marion Nestle explains, these studies are more about marketing than science; they are often paid for by companies that sell those foods. Whether it's a Coca-Cola-backed study hailing light exercise as a calorie neutralizer, or blueberry-sponsored investigators proclaiming that this fruit prevents erectile dysfunction, every corner of the food industry knows how to turn conflicted research into big profit. As Nestle argues, it's time to put public health first. Written with unmatched rigor and insight, Unsavory Truth reveals how the food industry manipulates nutrition science--and suggests what we can do about it"--